Seed populations of Striga species in Nigeria - Hartman, G.L.; Tanimonure, O.A. (1991)
Seeds of Striga asiatica and S. hermonthica were separated from soil using a wet sieve method with a 2.5 smallcap˜M sucrose flotation solution and 250- and 150-µm mesh screens. In 34 fields, the av. and range of seeds/100 g of soil were 8.2 and 0-75, resp. Seeds were recovered from 28 of the 34 fields sampled. Eighteen, six and four fields had 1-5, 6-20, and >21 seeds/100 g of soil, resp. The max. number of seeds/100 g of soil was 202, collected from one sample site in a field. Emerged S. asiatica, S. gesnerioides, and S. hermonthica were present in 28 fields. The av. number of seeds/plant produced by S. gesnerioides was 6.4 × 104, and the av. number of seeds/capsule was 604. Seed recovery and plant emergence were correlated at one site.